The Needs Of Bella Swan Running Her Love's Life In Breaking Dawn Movie 2011 Directed By Bil Condon: A Humanistic Perspective - Siwi, Gilang Fermata; , Drs. Abdillah Nugroho, M. Hum; , Dr. Anam Sutopo, M.Hum (2014)
The major issue of this study is is how is the need for love of Bella Swan reflected in Breaking Dawn movie?. The objective of this study is to analyze Breaking Down movie based on its structural elements that help the writer identify the narrative aspect and technical element of the major character, and to analyze the true love of the major chaacter in Breaking Down movie based on humanistic psychological perspective. The research is qualitative study. The researcher uses two data sources: primary data source and secondary data source. Primary data are taken from Breaking Down movie by Bill Condon. The secondary data are taken from other sources related to this movie such as, articles, movie review and other relevant information. The results of the study show; firstly, the casts who is dominant in supporting the major character (Bella Swan) such as Edward Cullen, Jacob Black, Carlisle Cullen, and Sam Uley. The plot if the movie consists of, first, exposition, the story begins in wedding of Bella Swan to Edward Cullen. Complication appears where the on the pregnancy times of Bella is coming and it will kill its mother. Resolution, when Bella is dying the pack led by Sam comes to Cullen's house; intending to attack the vampire's family. The point of view of Breaking Dawn, uses Bella's voice which makes sense that she is beginning to start the entire story. The theme of the movie is 'love as one human basic need can not be changed by others'. The setting of Breaking Dawn movie is in a certain place where vampire and werewolf usually lived. Based on humanistic psychological approach, The physiological needs of Bella appear related with her love feeling. The need of safety and security of Bella appears after she gets pregnant, they see. that Bella will not save, if she does not eat Blood. Bella needs to survive. Belonging need of Bella is that Bella needs moral support from her family. The self-esteem of Bella appears when she feels free and satisfied when she gets married with Edward. Self-actualization of Bella's where she really wants to take Edward as her husband and stand in front of him in marriage.